"Digital Generation" Utilization of Smartphones as Media for Student Learning Reading - Rahmat Saputra; Yusniar Yusniar (Proceedings of The ICECRS, 2020)
This study aims to improve students 'understanding of learning to read by utilizing smartphones as learning media and to see students' responses to learning by using learning media. The research method used in this research is observation to observe the learning process, tests to determine students' understanding of learning to read, and a questionnaire to see student responses. The results that have been obtained in this study are: 1) Students are more enthusiastic and active when following the teaching and learning process, 2) the results of the test are 17 students (85%) who are complete and 3 students (15%) who are not finished, 3) Sawang Elementary School 25 students' responses to smartphone-based learning media with good categories, which means the media is effectively used as a learning medium.